Workplace stress - Sharifah Intan Safina, Syed Zubir; Mohd Ghani, Awang (Pejabat Naib Canselor, 2009)
“Job stress can be defined as the harmful physical and emotional responses that occur when the requirements of the job do not match the capabilities, resources or needs of the worker. Job stress can lead to poor health and even injury.” [Stress At Work, United States National Institute of Occupational Safety and Health, Cincinnati, 1999.]